Report On Anthracnose Of Rauwolfia Serpentina (L.) Benth. Ex Kurz Caused By Colletotrichum Gloeosporioides (Penz.) Sacc. From Bangladesh - Yasmin, Zuhra; Shamsi, Shamim (Journal of the Asiatic Society of Bangladesh, Science, 2015)
During the tenure of May 2007 to July 2013 severe anthracnose symptom was recorded on leaves of Rauwolfia serpentina (L.) Benth. Ex Kurz. The frequency percentage of association of Colletotrichum gloeosporioides, was higher than any other fungi associated with symptomatic leaves. The frequently isolated fungus C. gloeosporioides was found to be pathogenic to respective plants when pathogenicity of the isolated fungus was tested following modified “detached leaf technique” and ’’spraying of spore suspension” methods. Present paper is the first report of anthracnose of R. serpentine from Bangladesh. Asiat. Soc. Bangladesh, Sci. 41(2): 183-192, December 2015